Quadricuspid Aortic Valve With Severe Aortic Regurgitation - Takumi Minatoya; Atsushi Hayashi; Hiroki Okamoto; Kohei Asada; Noriyuki Takashima; Tomoaki Suzuki; Yoshihisa Nakagawa (Clinical Case Reports)
ABSTRACT Whenever a quadricuspid aortic valve (QAV) was present, it was historically only identified during open heart surgery. However, recent advances in transthoracic echocardiography have made it possible to detect QAV preoperatively. Further evaluation using transesophageal echocardiography or computed tomography before open surgery may help guide the surgical treatment strategy.